Sumber Qawaid Fiqhiyyah Dalam Lintas Mazhab dan Pengembangannya Dalam Studi Hukum Islam - Rabiatul Adawiyah Nasution; Imamul Muttaqin (Yayasan Dar Arrisyah Indonesia, 2024)
Qawā'id fiqhiyyah constitute one of the essential methodological foundations in Islamic legal reasoning, functioning as a bridge between detailed juristic rulings (furū‘) and broader legal principles. Although numerous studies have examined Islamic legal maxims, most of them focus on individual schools of law or the application of universal legal maxims in specific legal fields. Comparative studies that comprehensively examine the primary sources of qawā'id fiqhiyyah across the four Sunni schools of law and analyze their contribution to the development of contemporary Islamic legal studies remain relatively limited. This article aims to analyze the principal sources of qawā'id fiqhiyyah within the Hanafi, Maliki, Shafi'i, and Hanbali schools while examining their methodological characteristics and their relevance to the contemporary development of Islamic law. This study employs normative legal research based on library research using historical, comparative, and doctrinal approaches. Primary data are derived from classical works of qawā'id fiqhiyyah representing each school of law, while secondary data consist of scholarly books and recent academic publications. The findings demonstrate that each school developed legal maxims according to its own epistemological framework and legal methodology, resulting in distinct patterns of legal reasoning despite sharing several universal principles. The comparative analysis further indicates that the diversity of legal maxims across the schools enriches Islamic legal methodology and provides a flexible framework for addressing contemporary legal issues in areas such as Islamic finance, digital technology, bioethics, environmental protection, and public policy. This study contributes to strengthening comparative studies of Islamic legal maxims and highlights their continuing significance as an adaptive methodology for contemporary Islamic legal development.